Diffraction for industries, businesses and health - García-Aranda, Miguel Ángel (My University, 2019)
Se adjunta abstract en PDF- PDF abstract is attached
Keywords: Rayos X - Difracción; Difracción; Powder diffraction; Industry; Quantitative phase analysis; Rietveld method